MAKNA FILOSOFIS WACANA KONVERSI AGAMA DI DESA PAKRAMAN PAKUSEBA TEGALALANG GIANYAR - I Nyoman Raka (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
The religious conversion discourse in Pakuseba is interesting to study; because tryingto change a person's beliefs, or a group of people is not easy work. But in fact, a number ofPakuseba citizens who have for many years embraced Hinduism, are now converting toChristianity. Certainly accompanied by changes in the philosophy of life of some converts.Knowing the philosophical meaning of religious conversion discourse becomes important,especially for the academics of the High School of Religious Studies. To know the philosophicalmeaning of conversion of religion can be done by understanding the process, and the reason ofreligious conversion in Pakuseba. There are three critical theories used in this research are:Discourse theory, Hegemony theory, and Deconstruction theory. With the theory of deconstructioncan be known the meaning of the text and the meaning of the context of religious conversiondiscourse; with hegemony can be known the process of hegemony of missionaries to the communityin Pakuseba, with discourse theory known philosophical meaning of religious conversiondiscourse. The results showed that the discourse of religious conversion in Pakuseba using theapproach of material discourse. Poor people who are hungry for education are generally caughtup in religious conversion efforts. Economic crashes and low understanding of religious teachingsopen up opportunities for religious conversion. This happened to a group of Pakuseba citizens.Philosophically speaking, the discourse of religious conversion is a meaningful transaction ofbelief, which originates from intentions out of the economic crush through education and leadsto conversion of religion. Conclusion, the discourse of conversion of religious meaningfultransaction confidence.